Logo design - Wiedemann, Julius (Koln Taschen, 2015)
"A good logo can glamorize just about anything. This sweeping compendium gathers diverse brand markers from around the world to explore the irrepressible power of graphic representation. Organized into chapters by theme, the catalog explores how text, image, and ideas distil into a logo across events, fashion, media, music, and retailers"--Provided by publisher.
Intro: Paul Middleton -- Creative industry -- Events & entertainment -- Fashion & Apparel -- Institutions, government & regional -- Media -- Music -- Retailers & food outlets -- Service & business -- Miscellaneous -- Imprint.
Keywords: Logos (Symbols) -- Design; Graphic arts; Commercial art